Analyzing and Defending Web Application Vulnerabilities through Proposed Security Model in Cloud Computing - Bisht, Prabhat; Pant, Devesh; Rauthan, Manmohan Singh (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.982973);" role="presentation">Security of web applications from attackers is one of a challenging task in cloud <span dir="ltr" style="left: calc(var(--scale-factor)*420.22px); top: calc(var(--scale-factor)*322.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942039);" role="presentation">computing infrastructure. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.973114);" role="presentation">Unsecure source code is one of a top reason for cyber-<span dir="ltr" style="left: calc(var(--scale-factor)*309.07px); top: calc(var(--scale-factor)*335.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961862);" role="presentation">attacks, due to which valuable data like username, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*349.01px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917992);" role="presentation">password, credit card information or even personal information related to aadhar enabled biometric system, can <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900917);" role="presentation">be compromised<span dir="ltr" style="left: calc(var(--scale-factor)*138.50px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940118);" role="presentation">. Most of the vulnerabilities in web application s<span dir="ltr" style="left: calc(var(--scale-factor)*333.91px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904537);" role="presentation">ource code is related to <span dir="ltr" style="left: calc(var(--scale-factor)*430.30px); top: calc(var(--scale-factor)*362.21px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941131);" role="presentation">Open Web Application <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96057);" role="presentation">Security Project (OWASP), <span dir="ltr" style="left: calc(var(--scale-factor)*190.25px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935945);" role="presentation">these vulnerabilities are <span dir="ltr" style="left: calc(var(--scale-factor)*292.49px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994078);" role="presentation">SQL, NoSQL, LDAP Injection<span dir="ltr" style="left: calc(var(--scale-factor)*421.42px); top: calc(var(--scale-factor)*375.41px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963324);" role="presentation">, Broken Authentication, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917523);" role="presentation">Sensitive data <span dir="ltr" style="left: calc(var(--scale-factor)*133.70px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881261);" role="presentation">exposure, <span dir="ltr" style="left: calc(var(--scale-factor)*176.57px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00016);" role="presentation">XML external e<span dir="ltr" style="left: calc(var(--scale-factor)*243.77px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940823);" role="presentation">ntities, broken access control, <span dir="ltr" style="left: calc(var(--scale-factor)*371.59px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955165);" role="presentation">security misconfigurati<span dir="ltr" style="left: calc(var(--scale-factor)*465.82px); top: calc(var(--scale-factor)*388.61px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945137);" role="presentation">on, Cross site <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942293);" role="presentation">scripting <span dir="ltr" style="left: calc(var(--scale-factor)*113.51px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938625);" role="presentation">(XSS), <span dir="ltr" style="left: calc(var(--scale-factor)*147.60px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884436);" role="presentation">Insecure <span dir="ltr" style="left: calc(var(--scale-factor)*188.00px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914499);" role="presentation">deserialization <span dir="ltr" style="left: calc(var(--scale-factor)*252.76px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*273.86px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949608);" role="presentation">insuf<span dir="ltr" style="left: calc(var(--scale-factor)*293.93px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981837);" role="presentation">ficient <span dir="ltr" style="left: calc(var(--scale-factor)*326.18px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952314);" role="presentation">monitoring <span dir="ltr" style="left: calc(var(--scale-factor)*377.01px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*397.99px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949797);" role="presentation">logging <span dir="ltr" style="left: calc(var(--scale-factor)*435.34px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.878167);" role="presentation">etc. <span dir="ltr" style="left: calc(var(--scale-factor)*456.09px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936556);" role="presentation">Vulnerable <span dir="ltr" style="left: calc(var(--scale-factor)*507.06px); top: calc(var(--scale-factor)*401.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.895691);" role="presentation">web <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925158);" role="presentation">applications are the hot spot for hackers. According to Symantec’s Internet Security <span dir="ltr" style="left: calc(var(--scale-factor)*414.70px); top: calc(var(--scale-factor)*415.13px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925663);" role="presentation">Threat Report published in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*428.33px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943773);" role="presentation">July 2017, more than 2 lakh attacks against websites occur each day and more than 76% websites hosted in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91967);" role="presentation">cloud contain un-<span dir="ltr" style="left: calc(var(--scale-factor)*142.10px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921691);" role="presentation">patched vulnerabilities. <span dir="ltr" style="left: calc(var(--scale-factor)*238.25px); top: calc(var(--scale-factor)*441.53px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902437);" role="presentation">This paper proposes a new innovative conceptual security tool name as <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*454.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941692);" role="presentation">SECUREWEB. <span dir="ltr" style="left: calc(var(--scale-factor)*139.22px); top: calc(var(--scale-factor)*454.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975304);" role="presentation">This tool will detect vulnerabilities in web application source code and automatically patch <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*467.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942516);" role="presentation">detected vulnerabilities and return secure source code free from any identified vulnerabilities. This tool works <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*481.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.97422);" role="presentation">on the concept of proxy based source code analyzer <span dir="ltr" style="left: calc(var(--scale-factor)*302.23px); top: calc(var(--scale-factor)*481.27px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00028);" role="presentation">SECUREEYE model for detecting OWASP Top 10 <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*494.47px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930189);" role="presentation">vulnerabilities and SECURESOLUTION model for auto patching of detected vulnerabilities.